The Use of E-Module Based on Higher Orther Thinking Skill (HOTS) Question to Improve Cognitive Learning Results College Students of Primary School Teachers - Nurhayati, Yeti; Setiawan, Wawan (Institut Keguruan dan Ilmu Pendidikan Siliwangi, 2022)
This research is motivated by the thinking ability of PGSD students at one university is still relatively low.This study aims to determine the use of Higher Order Thinking Skill (HOTS) -based e-module to improve cognitive learning outcomes of prospective elementary school teacher students. This research is a quantitative study with a quasi-experimental method and a nonequivalent control group design. The instrument used in this study was the validated e-module based on HOTS questions and test questions to measure the cognitive learning outcomes of prospective elementary school teacher students.Thepopulationinthisstudywerestudentsof2018prospectiveelementaryschoolteachersfor the Elementary School Teacher Education Study Program at a University in Bandung. The sampling technique is saturated samples. The data obtained were analyzed using descriptive analysis and inferential analysis of the one-sample t test and independent sample t test assisted by SPSS version 25. The results showed that the use of HOTS question-based e-module can improve the cognitive learning outcomes of prospective elementary school teacherstudents.